MANAGEMENT OF SOCIAL COMMUNITY OF INDONESIAN CHINESE MARGA IN BANTEN - I Ketut Damana (International Conference on Social and Islamic Studies, 2021)
This research is motivated by a decrease in the number of followers of social groups. The decline in followers shows a decrease in the decision of the followers of the Chinese clan social community that how the management of the Chinese clan social community is in the midst of the increasingly stringent community phenomenon based on the community management, the perception of the Chinese clan and the attitude of social needs. This study used descriptive qualitative method. Data were collected using the Miles & Hubarman model and interview techniques, with 6 people observing. The results showed that the management of the Chinese clan social community had no effect on the education sector, thus encouraging the implementation of mandarin courses, scholarships, library procurement and book review.